Recent advances in understanding the mechanisms by which sodium-glucose co-transporter type 2 inhibitors protect podocytes in diabetic nephropathy - Xinqi Chen; Mingjie Wang; Zhaoli Yan (Diabetology & Metabolic Syndrome)
Abstract Background Diabetes mellitus is associated with systemic damage across multiple organ systems, and an increasing number of patients are presenting with diabetic kidney disease as its initial manifestation. The onset and progression of diabetic nephropathy is closely associated with podocyte injury. Main body Sodium-glucose cotransporter type 2 (SGLT2) inhibitors, which can significantly reduce glucose levels as well as protecting against kidney damage, are therefore widely used for the clinical treatment of patients with diabetic kidney disease. An increasing body of research has revealed that the renal protective effect of SGLT2 inhibitors is primarily derived from their enhancement of podocyte autophagy and their inhibition of inflammation and podocyte apoptosis. Multiple signaling pathways are involved in these processes. Conclusion A deeper exploration of the renal protective effects of SGLT2 inhibitors and the underlying mechanisms will provide more solid theoretical support for their application in the prevention and treatment of diabetic kidney disease.